A kind of low expansion structural ceramic for aluminum industry and preparation method thereof
By combining the pretreated coal gangue and secondary aluminum ash, a matrix is formed and a low-expanded structural ceramic is generated through the sintering process, the existing refractory materials have been solved in the alternating environment of hot and cold, and have excellent mechanical properties under high temperature conditions, which broadens the application scenarios of secondary aluminum ash.
Patent Information
- Application Number
- CN202411163984.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-08-23
AI Technical Summary
The existing aluminum industrial refractory materials have volume changes in the alternating environment of hot and cold, which affects their thermal shock stability. At the same time, the secondary aluminum ash contains alkali metal oxides, which limits its application.
By combining the pretreated coal gangue and secondary aluminum ash, the specific surface area of the fine powder is increased by ball milling and stirring to form a matrix, and with the assistance of low-aluminum mullite aggregate, it reacts in situ through the sintering process to generate low-expanded structural ceramics.
The volume stability of ceramic materials in the low temperature stage is achieved, and excellent mechanical properties are shown under high temperature conditions, which broadens the application scenarios of secondary aluminum ash and meets the development requirements of energy conservation and consumption reduction and circular economy.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of refractory materials, and specifically discloses a low expansion structural ceramic for aluminum industry and a preparation method thereof. Background Art
[0002] During the aluminum and recycled aluminum smelting process, the floating aluminum slag formed by oxidation is called primary aluminum ash. Primary aluminum ash contains a large amount of metallic aluminum. After recycling, the remaining aluminum ash is called secondary aluminum ash. Secondary aluminum ash contains heavy metal elements and impurities such as AlN, which pollutes the atmosphere and soil and is an industrial hazardous waste. However, secondary aluminum ash also contains a large amount of aluminum oxide, which has economic value as a renewable resource.
[0003] Pyrocalcination is an important method for harmless treatment of secondary aluminum ash. After pyrocalcination, secondary aluminum ash is transformed into a material with aluminum oxide as the main component, also known as harmless secondary aluminum ash, which has the characteristics of high aluminum oxide content, irregular microstructure, high surface activity, etc., and has certain corrosion resistance, thermal shock resistance, thermal stability and high temperature resistance. However, due to the refining agents such as KCl and NaCl used in the aluminum casting process, the secondary aluminum ash contains a considerable amount of alkali metal oxides such as K2O and Na2O, which limits its application.
[0004] Mullite high-silica glass composite material is composed of mullite and SiO2 glass phases, contains no or very little quartz phase, has a low thermal expansion coefficient and excellent high-temperature performance. Due to the low melting temperature of aluminum and alloys, and the need to frequently open the furnace door to feed and slag removal during the production process, the aluminum-silicon refractory lining will be used in an alternating hot and cold environment. The quartz phase in the aluminum-silicon refractory will undergo volume changes, which is not conducive to the thermal shock stability of the refractory. The excellent comprehensive properties of mullite high-silica glass composite materials make it particularly suitable for refractory linings for aluminum casting reverberatory furnaces. The application of secondary aluminum ash to refractory materials for aluminum processing can broaden the application scenarios of secondary aluminum ash, which meets the requirements of energy conservation, consumption reduction and the development of a circular economy. In summary, it is of great significance to study a low-expansion structural ceramic for the aluminum industry with the addition of secondary aluminum ash. Summary of the invention
[0005] The object of the present invention is to provide a low expansion structural ceramic for aluminum industry and a preparation method thereof, so as to solve the problems raised in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solution: A method for preparing low expansion structural ceramics for aluminum industry: comprising the following steps: S1: calcining coal gangue at a low temperature of 400-500°C for 24-72 hours to remove impurities such as residual carbon in the coal gangue, then soaking it in a dilute acid solution for 3-5 hours to remove other oxide impurity components in the coal gangue, and baking it at 100-150°C for 24 hours to dehydrate and dry it to obtain pretreated coal gangue;
[0007] S2: pre-treated coal gangue and calcined secondary aluminum ash are added to a ball mill, and Φ5mm-Φ10mm corundum balls are used as ball milling media. The two materials are ball milled for at least 3 hours to mix the two materials evenly. The particle size of the mixed fine powder is measured after ball milling, and it is required to be at least 325 meshes. Otherwise, the ball milling time is extended to meet the requirements, thereby increasing the specific surface area of the two fine powders, improving the reaction activity, and facilitating sintering. After ball milling, a mixed dry powder is obtained; the mixed dry powder, secondary aluminum ash, silica powder, functional additives, binders, and admixtures are mixed to obtain a matrix; low-aluminum mullite aggregate is added, and the mixture is fully stirred for at least 5 minutes with a forced mixer to obtain a castable dry powder;
[0008] S3: Take dry powder and water of the casting material, add them into a forced mixer, stir for 3 to 5 minutes to obtain a mixed wet material; pour the mixed wet material into a mold for forced vibration molding, and after the material solidifies and naturally dries for at least 24 hours to have initial strength, remove it from the mold to obtain a sample; sinter it at 1000℃~1400℃ for 3 to 24h, cool it to room temperature with the furnace, and use the sintering and phase change effects of the low-melting alkali metal oxides in the pretreated coal gangue and secondary aluminum ash and the added potassium additives to cause the pretreated coal gangue and secondary aluminum ash in the matrix to react in situ to form a low-expansion structural ceramic product with mullite and high-silica glass as the main matrix.
[0009] More optimally, during the pretreatment of the gangue, the low-temperature calcination time of the gangue is 50 hours.
[0010] More optimally, the dilute acid solution is an aqueous solution of sulfuric acid or hydrochloric acid with a concentration of 3% to 5wt%; the soaking temperature is 30 to 50°C.
[0011] More optimally, the specific soaking process is: soaking at 40° C. for 4 hours, and the dilute acid solution is an aqueous solution of hydrochloric acid with a concentration of 4wt%.
[0012] More optimally, the castable dry powder includes the following raw materials, in parts by mass: 10-30 parts of calcined secondary aluminum ash, 5-15 parts of pretreated coal gangue, 0.1-2 parts of secondary aluminum ash, 1-10 parts of silica powder, 1-5 parts of functional additives, 3-6 parts of binders, 0.1-0.5 parts of admixtures, and 50-80 parts of low-aluminum mullite aggregate; in the mixed wet material, the amount of water added is 5-7% of the mass of the castable dry powder.
[0013] More optimally, in the mixed wet material, the amount of water added is 6% of the mass of the castable dry powder.
[0014] More optimally, the low aluminum mullite aggregate includes the following raw materials, calculated by weight: 15 to 35 parts of 3 to 5 mm low aluminum mullite aggregate, 15 to 35 parts of 1 to 3 mm low aluminum mullite aggregate, and 5 to 25 parts of 0.075 to 1 mm low aluminum mullite aggregate.
[0015] More optimally, the low-aluminum mullite aggregate has an Al2O3 content of 45-50% and a bulk density of 2.4-2.6 g / cm 3 The crystal phase composition is mainly mullite phase.
[0016] More optimally, the main chemical composition of the coal gangue is, by mass percentage, 55-65% SiO2, 20-30% Al2O3, 3-5% K2O, 1-3% Fe2O3, 0.5-2% MgO, and 0.1-1% Na2O.
[0017] More optimally, the main chemical composition of the secondary aluminum ash, by mass percentage, is: 10-20% Al, 10-15% AlN, 35-45% Al2O3, 5-10% MgO, 5-10% KCl, and 3-8% NaCl.
[0018] More optimally, the chemical composition of the calcined secondary aluminum ash includes the following raw materials, calculated by mass percentage: 60-80% Al2O3, 5-15% SiO2, 0.5-3% Fe2O3, 0.5-3% CaO, 1-5% K2O, and 0.5-3% Na2O.
[0019] More optimally, in the matrix, the mass ratio of Al2O3 to SiO2 is in the range of 2:1 to 1:1, so that the matrix is silicon-rich to a certain extent.
[0020] More optimally, the functional additives include natural minerals containing potassium feldspar, such as potassium-based bentonite, potassium carbonate, potassium sulfate, potassium hydroxide, or a combination thereof.
[0021] More optimally, the functional additive is potassium-based bentonite.
[0022] More optimally, the preparation of the potassium-based bentonite refers to the prior art, and specifically includes the following steps: take 10 parts of bentonite, crush it and pass it through a 30-mesh sieve, add it to a mixed aqueous solution of 2 parts of sodium chloride and lithium chloride (the concentration of the mixed aqueous solution of sodium chloride and lithium chloride is 0.15 mol / L, and the mass ratio of sodium chloride to lithium chloride is 1:1), stir for 5 hours, and separate the solid by a centrifuge to obtain the primary treated soil; dry and remove water from the above-mentioned primary treated soil, roast it at 220°C for 12 hours, add 2 parts of a potassium chloride aqueous solution with a concentration of 0.2 mol / L, stir for 5 hours, separate the solid by a centrifuge to obtain the solid, and dry it to obtain potassium-based bentonite.
[0023] More optimally, the silicon micropowder has a SiO2 content of ≥96%, a pH value of 6.5-7.5, and a C content of ≤1%.
[0024] More optimally, the binder is CA-70 pure calcium aluminate cement with Al2O3≥68% and CaO≤31%; the admixture includes one or a combination of sodium tripolyphosphate, sodium hexametaphosphate, and citric acid.
[0025] More optimally, the preparation of the pretreated coal gangue includes the following steps: S1: calcining the coal gangue at a low temperature of 400-500°C for 24-72 hours to remove impurities such as residual carbon in the coal gangue, then soaking it in a dilute acid solution for 3-5 hours to remove other oxide impurity components in the coal gangue, and baking it at 100-150°C for 24 hours to dehydrate and dry it to obtain coal gangue B; taking coal gangue B, adding water and ethanol, stirring evenly, heating to 40-60°C, adding vinyltrimethoxysilane, stirring for 4-6 hours, filtering and drying, and obtaining double-bonded coal gangue;
[0026] S2: taking double-bonded coal gangue, methyl acrylate, methyl methacrylate, acrylic acid, styrene, hydroxyethyl methacrylate, tert-butyl perbenzoate, dodecanethiol and propylene glycol methyl ether acetate, and mixing them to obtain a mixed solution; under a nitrogen atmosphere, at 140-145° C., dripping the mixed solution into a reaction kettle within 3-4 hours, and keeping the temperature and stirring continuously for 4-5 hours to obtain modified coal gangue;
[0027] S3: Take modified coal gangue, β-cyclodextrin, and triisopropanolamine, add them into water, stir evenly, add glutaryl dichloride aqueous solution dropwise within 20 to 30 minutes under nitrogen protection, stir and react at 25 to 30° C. for 10 to 12 hours, filter, and rotary evaporate to remove the solvent to obtain pretreated coal gangue.
[0028] More optimally, the double-bonded coal gangue comprises the following raw materials, by weight: 10 parts of coal gangue, 50-60 parts of water, 50-60 parts of ethanol, and 1-2 parts of vinyltrimethoxysilane;
[0029] The modified coal gangue comprises the following raw materials, calculated by weight: 30 to 35 parts of double-bonded coal gangue, 1.5 to 2 parts of methyl acrylate, 0.5 to 0.8 parts of methyl methacrylate, 4 to 5 parts of acrylic acid, 1.5 to 2 parts of styrene, 1 to 1.5 parts of hydroxyethyl methacrylate, 0.15 to 0.2 parts of tert-butyl perbenzoate, 0.03 to 0.05 parts of dodecanethiol, and 5 to 5.5 parts of propylene glycol methyl ether acetate;
[0030] The pretreated coal gangue includes the following raw materials, calculated by mass: 45-50 parts of modified coal gangue, 8-10 parts of β-cyclodextrin, 1-2 parts of triisopropanolamine, and 50-60 parts of water; the glutaryl dichloride aqueous solution includes the following raw materials, calculated by mass: 5-8 parts of glutaryl dichloride and 15 parts of water.
[0031] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses coal gangue and secondary aluminum ash as main materials, both of which are industrial solid wastes. Due to their chemical composition and the refining agents such as KCl and NaCl used in the recycling process, they contain a certain amount of alkali metal oxides (K2O, Na2O, etc.), which limits their application. The present invention applies them to the preparation of structural ceramics, and by controlling the addition amount of Al2O3 and SiO2 in the matrix composition, the matrix is made silicon-rich. During the sintering process, the alkali metal oxides contained in the secondary aluminum ash and the pre-treated coal gangue are used as As an additive, it acts as a low-temperature sintering promoter, reduces the sintering temperature to 1000℃~1400℃, and makes Al2O3 and SiO2 in the matrix react in situ to generate mullite phase, and the excess quartz phase SiO2 is converted into amorphous glass phase, and no quartz phase is generated; based on the small volume change of the glass phase with temperature, the material exhibits excellent volume stability at low temperature; as the temperature rises, the glass melts into liquid filling; based on the high temperature and high strength characteristics of the mullite phase, the material exhibits excellent mechanical properties under high temperature conditions, and the performance of the material under different temperature conditions can be optimized by adjusting the aluminum-silicon ratio of the matrix.
[0032] (2) The pretreated coal gangue is first modified with vinyltrimethoxysilane to obtain a double bond structure, and then subjected to a polymerization reaction to obtain a modified coal gangue with a surface grafted polyacrylic acid polymer, thereby improving the interface conditions and increasing its dispersibility in the mixed wet material. The raw material of the modified coal gangue includes hydroxyethyl methacrylate. After adding glutaryl dichloride as a cross-linking agent, the hydroxyl group can react with triisopropanolamine and β-cyclodextrin. Triisopropanolamine has a good grinding aid effect and has strong dispersibility, which is beneficial to further improve the strength of structural ceramics. β-cyclodextrin provides a certain viscosity, improves the degree of integration with the system, and helps to improve the stability of triisopropanolamine. In summary, the addition of pretreated coal gangue can further reduce the porosity and linear expansion coefficient of the product and improve its strength.
[0033] (3) The present invention uses secondary aluminum ash to replace metal aluminum powder, polypropylene chopped fibers, etc. as an explosion-proof agent for structural ceramics, and utilizes the metal Al, AlN, etc. contained in the secondary aluminum ash to react with water. The formula is as follows: Al+H2O→Al(OH)3+H2↑, AlN+H2O→Al(OH)3+NH3↑. The gas released by the reaction forms fine channels when it is discharged from the structural ceramics, making it difficult for the structural ceramics to explode when dehydrated during the baking process.
[0034] (4) The low expansion structural ceramics prepared by the present invention can be used as high temperature resistant lining materials for aluminum processing reverberatory furnaces. During the refining process of aluminum and its alloys, the refining agent volatilizes at high temperature and precipitates in the form of alkali metal oxides. The volatiles adhere to the lining material along with the flue gas, which promotes the in-situ generation of high silica glass phase of SiO2 in the lining material. The glass phase melts at high temperature and blocks the pores, thereby isolating the acid / alkaline atmosphere from continuing to penetrate into the lining, effectively improving the material's resistance to acid / alkaline atmosphere erosion;
[0035] (5) In summary, the present invention controls the aluminum-silicon ratio in the raw materials and rationally utilizes the properties of alkali metal oxides in industrial solid waste to use coal gangue and secondary aluminum ash for the preparation of structural ceramics, thereby broadening its application scenarios and meeting the development requirements of energy conservation, consumption reduction and circular economy. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] The following parts are by mass unless otherwise specified;
[0038] Example 1: S1: Pretreatment of coal gangue: calcining the coal gangue at 400°C to remove impurities such as residual carbon in the coal gangue, then immersing the coal gangue in a dilute acid solution to remove other oxide impurities in the coal gangue, and baking at 150°C for 24 hours to dehydrate and dry to obtain pretreated coal gangue;
[0039] S2: pre-treated coal gangue and calcined secondary aluminum ash are added to a ball mill, and corundum balls are used as ball milling media. The two materials are ball milled for at least 3 hours to mix the two materials evenly. The particle size of the mixed fine powder is measured after ball milling, and it is required to be at least 325 meshes. Otherwise, the ball milling time is extended to meet the requirements, thereby increasing the specific surface area of the two fine powders, improving the reaction activity, and facilitating sintering. After ball milling, a mixed dry powder is obtained; the mixed dry powder, secondary aluminum ash, silica powder, functional additives, binders, and admixtures are mixed to obtain a matrix; low-aluminum mullite aggregate is added, and the mixture is fully stirred for 5 minutes with a forced mixer to obtain a castable dry powder;
[0040] S3: Take the castable dry powder and water, add them into a forced mixer, stir for 5 minutes to obtain a mixed wet material; pour the mixed wet material into a mold for forced vibration molding, and after the material solidifies and has initial strength, remove it from the mold to obtain a sample; sinter it at 1300℃ for 5h, cool it to room temperature with the furnace, and use the sintering and phase change effects of the low-melting alkali metal oxides in the pretreated coal gangue and secondary aluminum ash and the added potassium functional additives to cause the pretreated coal gangue and secondary aluminum ash in the matrix to react in situ to form refractory low-expansion structural ceramics;
[0041] The castable dry powder includes the following raw materials, in parts by mass: 15 parts of calcined secondary aluminum ash, 10 parts of pretreated coal gangue, 0.5 parts of secondary aluminum ash, 4 parts of silica powder, 1.5 parts of functional additives, 4.5 parts of binders, 0.2 parts of admixtures, 25 parts of 3-5mm low-aluminum mullite aggregates, 18 parts of 1-3mm low-aluminum mullite aggregates, and 22 parts of 0.075-1mm low-aluminum mullite aggregates; the admixtures are sodium tripolyphosphate and citric acid, and the mass ratio of the two is 20:1; the functional additive is potassium-based bentonite.
[0042] Example 2: S1: Pretreatment of coal gangue: calcining the coal gangue at a low temperature of 400°C to remove impurities such as residual carbon in the coal gangue, then immersing the coal gangue in a dilute acid solution to remove other oxide impurities in the coal gangue, and baking at 150°C for 24 hours to dehydrate and dry to obtain coal gangue B; taking 10 parts of coal gangue B, adding 50 parts of water and 60 parts of ethanol, stirring evenly, heating to 50°C, adding 1.5 parts of vinyltrimethoxysilane, stirring for 4 to 6 hours, filtering and drying to obtain double-bonded coal gangue;
[0043] S2: 35 parts of double-bonded coal gangue, 1.5 parts of methyl acrylate, 0.8 parts of methyl methacrylate, 5 parts of acrylic acid, 1.5 parts of styrene, 1.5 parts of hydroxyethyl methacrylate, 0.2 parts of tert-butyl perbenzoate, 0.04 parts of dodecanethiol and 5.5 parts of propylene glycol methyl ether acetate were mixed to obtain a mixed solution; under a nitrogen atmosphere, at 140° C., the mixed solution was dripped into a reaction kettle within 4 hours, and the mixture was kept warm and stirred continuously for 5 hours to obtain modified coal gangue;
[0044] S3: Take 50 parts of modified coal gangue, 10 parts of β-cyclodextrin, and 2 parts of triisopropanolamine, add 50 parts of water, stir evenly, and under nitrogen protection, add glutaryl dichloride aqueous solution (8 parts of glutaryl dichloride, 15 parts of water) dropwise within 30 minutes, stir and react at 25°C for 12 hours, filter, and evaporate to remove the solvent to obtain pretreated coal gangue.
[0045] S4: pre-treated coal gangue and calcined secondary aluminum ash are added to a ball mill, and corundum balls are used as ball milling media. The two materials are ball milled for at least 3 hours to mix the two materials evenly. The particle size of the mixed fine powder is measured after ball milling, and it is required to be at least 325 meshes. Otherwise, the ball milling time is extended to meet the requirements, thereby increasing the specific surface area of the two fine powders, improving the reaction activity, and facilitating sintering. After ball milling, a mixed dry powder is obtained; the mixed dry powder, secondary aluminum ash, silica powder, functional additives, binders, and admixtures are mixed to obtain a matrix; low-aluminum mullite aggregate is added, and the mixture is fully stirred for 5 minutes with a forced mixer to obtain a castable dry powder;
[0046] S5: Take the castable dry powder and water, add them into a forced mixer, stir for 5 minutes to obtain a mixed wet material; pour the mixed wet material into a mold for forced vibration molding, and after the material solidifies and has initial strength, remove it from the mold to obtain a sample; sinter it at 1300℃ for 5h, cool it to room temperature with the furnace, and use the sintering and phase change effects of the low-melting alkali metal oxides in the pretreated coal gangue and secondary aluminum ash and the added potassium functional additives to cause the pretreated coal gangue and secondary aluminum ash in the matrix to react in situ to form refractory low-expansion structural ceramics;
[0047] The castable dry powder includes the following raw materials, in parts by mass: 15 parts of calcined secondary aluminum ash, 10 parts of pretreated coal gangue, 0.5 parts of secondary aluminum ash, 4 parts of silica powder, 1.5 parts of functional additives, 4.5 parts of binders, 0.2 parts of admixtures, 25 parts of 3-5mm low-aluminum mullite aggregates, 18 parts of 1-3mm low-aluminum mullite aggregates, and 22 parts of 0.075-1mm low-aluminum mullite aggregates; the admixtures are sodium tripolyphosphate and citric acid, and the mass ratio of the two is 20:1; the functional additive is potassium-based bentonite.
[0048] Comparative Example 1 (increasing the amount of secondary aluminum ash, not adding pretreated coal gangue, changing the ratio of Al2O3 to SiO2 in the matrix, and the remaining method steps are consistent with Example 1): S1: Take calcined secondary aluminum ash and add it to a ball mill, use Φ5mm~Φ10mm corundum balls as ball milling media, ball mill for at least 3 hours, take out and measure the particle size of the mixed fine powder, which is required to be at least 325 mesh, otherwise the ball milling time is extended to meet the requirements, and the mixed dry powder is obtained after the ball milling; the mixed dry powder, secondary aluminum ash, silica powder, functional additives, binders, and admixtures are mixed to obtain a matrix; low-aluminum mullite aggregate is added, and it is fully stirred for 5 minutes with a forced mixer to obtain a castable dry powder;
[0049] S2: Take the castable dry powder and water, add them into a forced mixer, stir for 5 minutes to obtain a mixed wet material; pour the mixed wet material into a mold for forced vibration molding, and after the material solidifies and has initial strength, remove it from the mold to obtain a sample; sinter it at 1300℃ for 5h, cool it to room temperature with the furnace, and use the sintering and phase change effects of the low-melting alkali metal oxides in the pretreated coal gangue and secondary aluminum ash and the added potassium functional additives to cause the pretreated coal gangue and secondary aluminum ash in the matrix to react in situ to generate refractory low-expansion structural ceramics;
[0050] The castable dry powder includes the following raw materials, in parts by mass: 25 parts of calcined secondary aluminum ash, 0.5 parts of secondary aluminum ash, 4 parts of silica powder, 1.5 parts of functional additives, 4.5 parts of binders, 0.2 parts of admixtures, 25 parts of 3-5 mm low aluminum mullite aggregate, 18 parts of 1-3 mm low aluminum mullite aggregate, and 22 parts of 0.075-1 mm low aluminum mullite aggregate.
[0051] Comparative Example 2: (the amount of functional additives and the sintering temperature are changed, and the other method steps are consistent with Example 1): S1: pretreatment of coal gangue: calcining the coal gangue at a low temperature of 400° C. to remove impurities such as residual carbon in the coal gangue, then immersing the coal gangue in a dilute acid solution to remove other oxide impurity components in the coal gangue, and baking at 150° C. for 24 hours to dehydrate and dry to obtain pretreated coal gangue;
[0052] S2: pre-treated coal gangue and calcined secondary aluminum ash are added to a ball mill, and corundum balls are used as ball milling media. The two materials are ball milled for at least 3 hours to mix the two materials evenly. The particle size of the mixed fine powder is measured after ball milling, and it is required to be at least 325 meshes. Otherwise, the ball milling time is extended to meet the requirements, thereby increasing the specific surface area of the two fine powders, improving the reaction activity, and facilitating sintering. After ball milling, a mixed dry powder is obtained; the mixed dry powder, secondary aluminum ash, silica powder, functional additives, binders, and admixtures are mixed to obtain a matrix; low-aluminum mullite aggregate is added, and the mixture is fully stirred for 5 minutes with a forced mixer to obtain a castable dry powder;
[0053] S3: Take the castable dry powder and water, add them into a forced mixer, stir for 5 minutes to obtain a mixed wet material; pour the mixed wet material into a mold for forced vibration molding, and after the material solidifies and has initial strength, remove it from the mold to obtain a sample; sinter it at 1200℃ for 5h, cool it to room temperature with the furnace, and use the sintering and phase change effects of the low-melting alkali metal oxides in the pretreated coal gangue and secondary aluminum ash and the added potassium functional additives to cause the pretreated coal gangue and secondary aluminum ash in the matrix to react in situ to form refractory low-expansion structural ceramics;
[0054] The castable dry powder includes the following raw materials, in parts by mass: 15 parts of calcined secondary aluminum ash, 10 parts of pretreated coal gangue, 0.5 parts of secondary aluminum ash, 4 parts of silica powder, 0.5 parts of functional additives, 4.5 parts of binders, 0.2 parts of admixtures, 25 parts of 3-5mm low-aluminum mullite aggregates, 18 parts of 1-3mm low-aluminum mullite aggregates, and 22 parts of 0.075-1mm low-aluminum mullite aggregates; the admixtures are sodium tripolyphosphate and citric acid, and the mass ratio of the two is 20:1; the functional additive is potassium-based bentonite.
[0055] Comparative Example 3 (the raw materials in the castable dry powder were adjusted, and the other method steps were consistent with Example 1): S1: pretreatment of coal gangue: calcining the coal gangue at a low temperature of 400° C. to remove impurities such as residual carbon in the coal gangue, then immersing the coal gangue in a dilute acid solution to remove other oxide impurity components in the coal gangue, and baking at 150° C. for 24 hours to dehydrate and dry to obtain pretreated coal gangue;
[0056] S2: pre-treated coal gangue and calcined secondary aluminum ash are added to a ball mill, and corundum balls are used as ball milling media. The two materials are ball milled for at least 3 hours to mix the two materials evenly. The particle size of the mixed fine powder is measured after ball milling, and it is required to be at least 325 meshes. Otherwise, the ball milling time is extended to meet the requirements, thereby increasing the specific surface area of the two fine powders, improving the reaction activity, and facilitating sintering. After ball milling, a mixed dry powder is obtained; the mixed dry powder, secondary aluminum ash, silica powder, functional additives, binders, and admixtures are mixed to obtain a matrix; low-aluminum mullite aggregate is added, and the mixture is fully stirred for 5 minutes with a forced mixer to obtain a castable dry powder;
[0057] S3: Take the castable dry powder and water, add them into a forced mixer, stir for 5 minutes to obtain a mixed wet material; pour the mixed wet material into a mold for forced vibration molding, and after the material solidifies and has initial strength, remove it from the mold to obtain a sample; sinter it at 1300℃ for 5h, cool it to room temperature with the furnace, and use the sintering and phase change effects of the low-melting alkali metal oxides in the pretreated coal gangue and secondary aluminum ash and the added potassium functional additives to cause the pretreated coal gangue and secondary aluminum ash in the matrix to react in situ to form refractory low-expansion structural ceramics;
[0058] The castable dry powder includes the following raw materials, in parts by mass: 20 parts of calcined secondary aluminum ash, 5 parts of pretreated coal gangue, 2 parts of secondary aluminum ash, 3 parts of silica powder, 1 part of functional additives, 4.5 parts of binders, 0.2 parts of admixtures, 25 parts of 3-5mm low-aluminum mullite aggregates, 18 parts of 1-3mm low-aluminum mullite aggregates, and 22 parts of 0.075-1mm low-aluminum mullite aggregates; the admixtures are sodium tripolyphosphate and citric acid, and the mass ratio of the two is 20:1; the functional additive is potassium carbonate.
[0059] In the above embodiments, the test methods used are conventional methods unless otherwise specified; the raw materials used are commercially available unless otherwise specified, and the sources of the raw materials are as follows: silica powder (Aiken 951U silica powder); low aluminum mullite aggregate (Shandong Refractory Materials Group, M50); sodium tripolyphosphate (food grade); citric acid (food grade).
[0060] Experiment: Through X-ray diffraction analysis, the crystal phase in the matrix of Example 1 is mullite phase, without quartz phase, and the mullite phase grows well. The apparent porosity of the product is 15.7%, the cold compressive strength of the product is 102MPa, and the cold flexural strength is 11.5MPa; the average linear expansion coefficient at 500-1000℃ is 3.4×10 -6 / ℃;
[0061] The crystal phase in the matrix of Example 2 is mullite phase, without quartz phase, and the mullite phase grows well. The apparent porosity of the product is 13.2%, the cold compressive strength of the product is 111MPa, the cold flexural strength is 12.3MPa; the average linear expansion coefficient at 500-1000℃ is 3.0×10 -6 / ℃;
[0062] The crystal phases in the matrix of Comparative Example 1 are corundum phase and mullite phase, the matrix is rich in aluminum, and there is no quartz phase. The apparent porosity of the product is 20.5%, there are many pores, and the pores are not well filled. The cold compressive strength of the product is 115MPa, the cold flexural strength is 11.9MPa; the average linear expansion coefficient at 500-1000℃ is 5.1×10 -6 / ℃;
[0063] The crystal phases in the matrix of Example 1 in the matrix of Comparative Example 2 are mullite and cristobalite phases, and the cristobalite phase is not transformed or the transformation is incomplete. The apparent porosity of the product is 18.9%. The cold compressive strength of the product is 95MPa, and the cold flexural strength is 9.8MPa; the average linear expansion coefficient at 500-1000℃ is 4.8×10 -6 / ℃;
[0064] The matrix of comparative example 3 has a crystalline phase of mullite, without quartz phase, but the mullite phase has small grains and poor growth, and the apparent porosity of the product is 17.5%. The cold compressive strength of the product is 93MPa, the cold flexural strength is 10.3MPa; the average linear expansion coefficient at 500-1000℃ is 3.9×10 -6 / ℃.
[0065] Conclusion: By utilizing the in-situ reaction between coal gangue and secondary aluminum ash, low expansion structural ceramics with mullite and high silica glass as the main matrix are formed, which has good performance and broadens the application scenarios of secondary aluminum ash, and meets the development requirements of energy conservation and consumption reduction and circular economy; it can be seen from Example 2 that when the dispersibility of each raw material is improved, the porosity and linear expansion coefficient can be effectively reduced; it can be seen from the comparative example that the amount of raw materials added needs to be controlled, and the amount of each raw material added in the present invention is of great significance.
[0066] Finally, it should be noted that the above is only a preferred embodiment of the present invention, but the protection scope of this application is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the spirit and principle of the present invention and within the technical scope disclosed in this application should be included in the protection scope of this application; in the absence of conflict, the embodiments of this application and the features in the embodiments can be combined with each other. Therefore, the protection scope of this application shall be based on the protection scope of the claims.
Claims
1. A method for preparing low expansion structural ceramics for aluminum industry, characterized in that: The following steps are involved: S1: calcining the coal gangue at 400-500°C for 24-72 hours, soaking it in a dilute acid solution for 3-5 hours, and baking it at 100-150°C for 24 hours to dehydrate and dry it to obtain pretreated coal gangue; S2: Take pretreated coal gangue and calcined secondary aluminum ash, mix them, and ball-mill them to a particle size of ≥325 mesh to obtain a mixed dry powder; mix the mixed dry powder, secondary aluminum ash, silica powder, functional additives, binders, and admixtures to obtain a matrix; add low-aluminum mullite aggregate, stir well, and obtain a castable dry powder; S3: Take the castable dry powder, add water, stir for 3-5 minutes to obtain a mixed wet material; pour the mixed wet material into a mold for forced vibration molding, and after natural curing for at least 24 hours, remove the mold to obtain a sample; sinter at 1000℃~1400℃ for 3-24h, cool to room temperature with the furnace, and obtain a low expansion structural ceramic; The castable dry powder includes the following raw materials, by weight: 10-30 parts of calcined secondary aluminum ash, 5-15 parts of pretreated coal gangue, 0.1-2 parts of secondary aluminum ash, 1-10 parts of silica powder, 1-5 parts of functional additives, 3-6 parts of binders, 0.1-0.5 parts of admixtures, and 50-80 parts of low-aluminum mullite aggregates; in the mixed wet material, the amount of water added is 5-7% of the mass of the castable dry powder; The functional additive is potassium-based bentonite; the binder is CA-70 pure calcium aluminate cement with Al2O3≥68% and CaO≤31%; the admixture includes one or a combination of sodium tripolyphosphate, sodium hexametaphosphate, calcium lignin sulfonate and citric acid.
2. The method for preparing low expansion structural ceramics for aluminum industry according to claim 1, characterized in that: The low aluminum mullite aggregate comprises the following raw materials, calculated by weight: 15 to 35 parts of 3 to 5 mm low aluminum mullite aggregate, 15 to 35 parts of 1 to 3 mm low aluminum mullite aggregate, and 5 to 25 parts of 0.075 to 1 mm low aluminum mullite aggregate.
3. The method for preparing low expansion structural ceramics for aluminum industry according to claim 1, characterized in that: The main chemical composition of the coal gangue is calculated by mass percentage: 55-65% SiO2, 20-30% Al2O3, 3-5% K2O, 1-3% Fe2O3, 0.5-2% MgO, and 0.1-1% Na2O.
4. The method for preparing low expansion structural ceramics for aluminum industry according to claim 1, characterized in that: The main chemical composition of the secondary aluminum ash, by mass percentage, is: 10-20% Al, 10-15% AlN, 35-45% Al2O3, 5-10% MgO, 5-10% KCl, 3-8% NaCl; the chemical composition of the calcined secondary aluminum ash, by mass percentage, is: 60-80% Al2O3, 5-15% SiO2, 0.5-3% Fe2O3, 0.5-3% CaO, 1-5% K2O, 0.5-3% Na2O.
5. The method for preparing low expansion structural ceramics for aluminum industry according to claim 1, characterized in that: In the matrix, the mass ratio of Al2O3 to SiO2 is (1~2):
1.
6. The low expansion structural ceramics prepared according to the method for preparing low expansion structural ceramics for aluminum industry according to any one of claims 1 to 5.
Citation Information
Patent Citations
Modified coal gangue aggregate concrete
CN107686309A
Ceramsite sand produced by using coal gangue and processing technology of ceramsite sand
CN109942275A